Palladium(II) Catalyzed Oxidation of Methyl Amine by N-Bromosuccinimide in Alkaline Medium : A Kinetic and Mechanistic Study - Kumar, Ashutosh; Pratap, Bhanu (Asian Journal of Chemistry, 2012)
The kinetics of Pd(II) catalyzed oxidation of methyl amine by alkaline solution of N-bromosuccinimide (NBS) in the presence of mercuric acetate as scavenger is investigated in the temperature range 30-45 ºC. First order kinetics in the lower concentration range of N-bromosuccinimide was observed to tend to zero order at its higher concentrations. The reaction follow identical kinetics, being zero order in substrate and [OH–]. A positive effect of variation of palladous chloride was observed while addition of succinimide and mercuric acetate did not affect the rate constant of reaction. The variation of ionic strength of the medium and [Cl–] showed zero effect on the reaction rate. The oxidation product formed formaldehyde formed was detected by spot test and 2,4-dinitrophenyl hydrazine test. Various thermodynamic parameters have been computed. A suitable mechanism, consistent with the kinetic observation has been proposed.